Comparative analysis of education systems: innovative pedagogical technologies - Шандрук Світлана; Shandruk Svitlana; Радул Валерій; Radul Valerii (Видавництво «Код», 2025)
Abstract. Integration of Ukraine into the global educational space, the need to study and implement world experience in the field of professional training of specialists require comparative research and analysis of foreign experience in training specialists in higher professional training systems, in the countries of the European Union and the USA. The results of such research will provide a fairly complete picture of the modern system of higher professional education in the EU and the USA, its content, organizational forms, technologies, internal and external factors of evolution, which will contribute to understanding, generalization and implementation of innovative searches, techniques and technologies for training specialists into the practice of modern professional training. A systems approach is a general method (modern general scientific methodology) of research and cognition of complex objects (systems), which is used in all areas of science, technology, management, etc. Systems analysis implements cognitive and methodological functions. It acts as an integral set of relatively simple methods and techniques of cognition and transformation of reality. The methodology of systems analysis is a rather complex set of principles, approaches, concepts, specific methods and techniques. As a simple version of the system analysis methodology, the following sequence can be considered: problem formulation; system structuring; model construction; model research. System analysis uses specific scientific tools. It consists of the following methods: informal heuristic (methods of scenarios, expert assessments, diagnostics, «cross» comparisons); graphical («goal tree», network, matrix methods); quantitative (economic analysis, cost-effectiveness analysis, statistical methods, morphological analysis, method of aggregating variables into complex factors). The ultimate goal of systems analysis is to assist in understanding and solving an existing problem, which boils down to finding and choosing a solution to the problem.

Резюме. Інтеграція України у світовий освітній простір, необхідність вивчення й упровадження світового досвіду в галузі професійної підготовки фахівців потребують компаративістських досліджень та аналізу зарубіжного досвіду підготовки спеціалістів в системах вищої професійної підготовки, в країнах Європейського Союзу та США. Результати таких досліджень дадуть досить повну картину сучасної системи вищої професійної освіти в ЄС та США, її змісту, організаційних форм, технологій, внутрішніх та зовнішніх чинників еволюції, що сприятиме осмисленню, узагальненню та впровадженню у практику сучасної професійної підготовки інноваційних пошуків, технік та технологій підготовки фахівців.
Компаративний аналіз систем освіти: інноваційні педагогічні технології
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: comparative analysis; education systems; systems approach; innovative technologies; systems analysis; scientific tools